Synergy in resolving border disputes after regional expansion: a case study of Gampong Meurandeh Dayah, Langsa City - Aliah, Fijanatin; Ulya, Zaki; Natsir, Muhammad (Geuthèë Institute, Aceh, 2025)
The determination of village boundaries is a crucial aspect of village governance to ensure legal certainty, administrative order, and the prevention of conflicts between villages. However, in practice, boundary disputes still frequently occur, as experienced by Gampong Meurandeh Dayah, Langsa Lama District, Langsa City, following the regional expansion in 2010. The lack of clear administrative boundaries has led to various issues, including land ownership disputes, difficulties in resource management, and obstacles to public service delivery. This study employs an empirical legal method with a sociological approach. Data were collected through field observations, interviews with village officials, and an analysis of relevant regulations, such as Law No. 6 of 2014 on Villages and Minister of Home Affairs Regulation No. 45 of 2016. The findings indicate that efforts to resolve the dispute have been undertaken, including field inspections and the creation of a territorial map, but these have not yet resulted in final legal certainty. A multi-faceted approach is required, involving administrative measures through boundary remapping, legal measures through binding village regulations, and social measures through mediation and customary deliberation. These steps are expected to resolve the boundary dispute fairly and sustainably.